Reducing Environmental Impact in Automated Waste Collection through Optimization and User Feedback Scheduling the emptying process to reduce energy consumption and changing user behavior - Ljunggren, Elin; Gustafsson, Emma (My University, 2017)
The automated vacuum waste collection system is an efficient way of handling waste in modern cities which is more sustainable than conventional systems. However, the environmental impact can be further reduced in the areas of system operation since the system consumes a substantial amount of energy where most of it is needed for the emptying process. One way of reducing the energy needed is to schedule the emptying procedure in a more efficient manner. Another way would be to stimulate reduction of waste production. The system has a graph structure in the shape of a tree where waste enters through the leaf nodes. During the emptying procedure, waste is transported to the root node, that is the collection station, by air suction. To be able to decide when an emptying sequence should be initiated and which type of waste and individual waste inlets should be included, the tree needs to be traversed and evaluated. Our method can be seen as a scheduling algorithm inspired by ideas from online optimization, since the system is scanned continuously to see if an emptying process should be initiated. Once an emptying process is initiated, the emptying sequence is performed according to dynamic programming principles. The algorithms have been simulated and then compared to the statistics for the current procedure during January 2017. The best result shows an approximate improvement of 37.6% less kWh than current monthly use. Another way to reduce the energy consumption is by lowering the amount of waste in the system by helping users gain insight in their waste generation. Less waste generated by users will lead to a lower demand on the system and fewer emptyings will be required. The goal was to create a prototype that can be used for creating incentive for reducing waste generation. Our solution to achieve this is a shell for a web application easily scaled to mobile screens.
Keywords: Data- och informationsvetenskap; Computer and Information Science